2021
DOI: 10.1016/j.metop.2021.100140
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effects of Anethum graveolens on liver oxidative stress and cholesterol 7 alpha-hydroxylase levels in non-alcoholic fatty liver disease (NAFLD) rat models

Abstract: Background High-fat high-cholesterol diet induces a phenotype similar to non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) in humans. In NAFLD and NASH, cholesterol and bile acid metabolisms are impaired to accumulate lipids and toxic bile acids along with cholestatic hepatic damage. Recently, the use of herbal-derived cholesterol lowering products has attracted much attention as possible therapeutic strategies for NAFLD. Hence, the aim of this study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, further studies are required to determine the protective effects of PVA/AGE against tissue peroxidation. Abbasi et al 30 showed that AGE protected the liver against oxidative stress and augmented its function. Shafaei et al 31 showed that AGE could alleviate cadmium-induced oxidative stress in the liver, kidney, and brain of mice primarily through its carvone and limonene content.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are required to determine the protective effects of PVA/AGE against tissue peroxidation. Abbasi et al 30 showed that AGE protected the liver against oxidative stress and augmented its function. Shafaei et al 31 showed that AGE could alleviate cadmium-induced oxidative stress in the liver, kidney, and brain of mice primarily through its carvone and limonene content.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that excessive accumulation of cholesterol in the blood leads to increased reactive oxygen species (ROS) production ( Li et al, 2020 ), and these highly reactive species mediate low-grade inflammation ( Reyes-Gordillo et al, 2017 ) ( Liao et al, 2021 ) ( Incalza et al, 2018 ). Systematic oxidative stress and inflammatory response impair lipid metabolism, and thus, lipids accumulate in the liver ( Abbasi et al, 2021 ). Therefore, reducing the oxidative stress and the inflammatory response is an important strategy to reduce hepatic lipid deposition and protect the liver in hypercholesterolemic rats.…”
Section: Introductionmentioning
confidence: 99%